(3eeGQSI GdCdYGH GdEdcJQhfjI h YdGbJgG HHYV GdeTcdGJ GdSdhcjI h GdGfaYGdjI dOi GdCWaGd ai eQMdI GdQhVI (B/ s - (3SMQ OShbi eMeO GdWGgQs; (3efGd YHOGdfYje eMeO Wg (B: s; (3fajSI ahRi YeQ (B: s ((3GdbGgQI (B: s (3SMQ OShbi eMeO GdWGgQ (B: s, 2021)
(3gOaJ GdOQGSI GdMGdjI Edi GdJYQa Ydi eeGQSI GdCdYGH GdEdcJQhfjI h YdGbJgG HHYV GdeTcdGJ GdSdhcjI h GdGfaYGdjI dOi CWaGd GdQhVI(B: (3h gPg GdeTcdGJ eJeKdI ai (B((3GdSdhc GdYOhGfi(B: (3GdGfSMGH GdGLJeGYi(B: (3GdYfGO(B: (3GdZVH(B: (3GdNha(B: (3Gdbdb(B) (3h bO WHbJ GdOQGSI Ydi YjfI echfI ef (B(195) (3WadG h WadI ef CWaGd GdQhVI GdPjf JJQGhM CYeGQge Hjf (B(5-7) (3SfhGJ(B: (3h bO GSJNOeJ GdOQGSI ebjGS GdeTcdGJ GdSdhcjI h GdGfaYGdjI dCWaGd GdQhVI hjTJed Ydi GdeTcdGJ GdBJjI (B((3GdSdhc GdYOhGfi(B: (3GdGfSMGH GdGLJeGYi(B: (3GdYfGO(B: (3GdZVH(B: (3GdNha(B: (3Gdbdb(B): (3h ebjGS GdCdYGH GdEdcJQhfjI h jTJed Ydi (B((3GdOhGaY GdEjLGHjI deeGQSI GdCdYGH(B: (3GdOhGaY GdSdHjI deeGQSI GdCdYGH(B: (3BKGQ eeGQSI GdCdYGH GdEdcJQhfjI(B): (3h GSJeGQI JMdjd eMJhi GdCdYGH GdEdcJQhfjI (B((3LejYge ef EYOGO GdHGMKI(B). (3h bO CTGQJ fJGFL GdOQGSI Edi hLhO YdGbI GQJHGWjI WQOjI h OGdI EMUGFjG YfO eSJhi (B(0.05) (3Hjf GdeTcdGJ GdSdhcjI dOi GdCWaGd ceG JOQcgG cd ef GdeYdeI h GdCe h eJZjQ Ref eeGQSI GdCdYGH GdEdcJQhfjI dOi CWaGd GdQhVI(B. (3HjfeG dG JhLO YdGbI GQJHGWjI h OGdI EMUGFjG YfO eSJhi (B(0.05) (3Hjf GdeTcdGJ GdGfaYGdjI dOi GdCWaGd ceG JOQcgG cd ef GdeYdeI h GdCe h HbjI CHYGO eeGQSI GdCdYGH GdEdcJQhfjI dOi CWaGd GdQhVI(B. (3h hLhO JCKjQ ehLH (B((3OGd YfO eSJhi(B0.01) (3dcd ef HYOi GdOhGaY GdSdHjI(B: (3h BKGQ eeGQSI GdCdYGH GdEdcJQhfjI ef GdOQLI GdcdjI ddeTcdGJ GdSdhcjI dOi GdCWaGd ceG JOQcgG GdCegGJ h GdeYdeGJ(B. (3ceG jhLO JCKjQ ehLH (B((3OGd YfO eSJhi (B0.01) (3dHYO GdOhGaY GdSdHjI abW(B: (3ai GdOQLI GdcdjI ddeTcdGJ GdGfaYGdjI dOi GdCWaGd ceG JOQcgG GdCegGJ h GdeYdeGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe Yde GdfaS GdEQTGOis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCdYGH GdEdcJQhfjIs; (3GdeTcdGJ GdSdhcjI h GdGfaYGdjIs; (3Wad GdQhVIs